Climate change and climate variability - Alves, Lincoln Muniz; Fowler, Hayley; Barreto, Naurinete de Jesus da Costa; Llopart, Marta [UNESP] (Elsevier, 2021)
Climate extremes, as recurring events, are the result of natural climate variability (including phenomena such as El Niño), which can have significant local and regional impacts on the society and the environment. These events are typically related to unusually high or low temperature, prolonged dry or wet conditions, heavy precipitation, or extreme winds. Recently, there has been considerable debate about the possible consequences of warming of the atmosphere for terrestrial ecosystems and societies, particularly related to changes in frequency, intensity, spatial extent, and duration of climate extremes over most land areas. This chapter provides an overview of the state of knowledge concerning the science of climate variability and climate extremes, emphasizing both present and past climate conditions and the projected changes over the 21st century. Science-based information based on robust findings and relevant uncertainties on changing extremes can provide useful information for sectorial planning, disaster risk prevention, and overall reduction of societal vulnerability related to climate and weather extremes.
Keywords: Climate change; Climate extremes; Climate variability; Precipitation